Wills Formalities versus Testator's Intention Functional model of effective testation for informal wills - Załucki, Mariusz (2021)
In recent years in particular, as a result of the very rapid development of various technologies, the phenomenon of so-called informal wills has appeared on a large scale in the practice of succession law. These are wills made by testators who, when disposing of their assets in the event of their death, do not make use of the forms of will provided for by the law. This is most often the result of ignorance or confusion as to the admissibility of a particular method of disposing of assets in the event of their death. In the light of the relevant provisions such a will is frequently invalid. Despite clear and convincing evidence and testation intentions, the testator's last will does not produce any legal effects regarding his estate. The inappropriateness of this kind of solutions was shown, among others, during the COVID-19 pandemic, when the need for making last wills has increased significantly, and has rarely been executed in a manner consistent with the formalities. Therefore, the main objective of this work is to design such a normative solution which could function in the provisions of succession law as one that constructs the legal figure of the form of a will.